Ultrasound screening for cholangiocarcinoma could detect premalignant lesions and early-stage diseases with survival benefits: a population-based prospective study of 4, 225 subjects in an endemic area. Issue 1 (December 2016) - Sungkasubun, Prakongboon; Siripongsakun, Surachate; Akkarachinorate, Kunlayanee; Vidhyarkorn, Sirachat; Worakitsitisatorn, Akeanong; Sricharunrat, Thaniya; Singharuksa, Sutida; Chanwat, Rawisak; Bunchaliew, Chairat; Charoenphattharaphesat, Sirima; Molek, Ruechuta; Yimyaem, Maneenop; et al.
Abstract Background Thailand has a high incidence of cholangiocarcinoma (CCA), particularly in the north and northeastern regions. Most CCA patients come at a late, unresectable stage and presently no optimal screening test for CCA has been established. We determined the prevalence of CCA in a remote northern village and explored if screening could lead to early detection and survival benefits. Methods A 5-year population-based study was started in October, 2011 for consented Thai individuals, aged 30–60 years. The screening program comprised blood testing, stool examination and serial ultrasonography every 6 months. Results During the first 3 years, 4, 225 eligible individuals were enrolled. CCA was detected in 32 patients, with a mean age of 51.9 years (41–62 years), and 21/32 cases were at a curative resectable stage. The prevalence rate of CCA was 165.7 per 100, 000 and one- and two-year incidence rate was 236.7/100, 000 and 520.7/100, 000, respectively. One- and 2-year overall survival rates of CCA patients were 90.9 and 61.5 %, respectively. Prognosis was better in resectable cases with 100 % 1-year and 77.8 % 2-year survival rates. Interestingly, premalignant pathological lesions (stage 0) were identified in 11 cases with 100 % 3-year survival rate. Serum biomarkers and alkaline phosphatase were not sufficient to detect early-stage disease. In 22 patients, stool samples were positive forOpisthorchis viverrini, based on polymerase chain reaction. Conclusion Detection of premalignant lesions and early-stage resectable CCA by ultrasonography resulted in improved clinical outcome. Ultrasonography should be offered as a first screening tool for CCA in an endemic area until other useful biological markers become available.